Green Growth, Green Practice, Green Business Antecedent And Conclusion To Drive Firm Value : A Conceptual Model - Rajayana Ades; Sukrisno Sukrisno; F. Pambudi Widiatmaka (UNIVED Press, 2022)
This study is aimed To maximize the value of the firm, various antecedents are needed for the driver, the various antecedents offered are expected to be a key factor in increasing the value of the firm. This research seeks to build a conceptual model for increasing the value of the firm. corporate sustainability performance and Green Business. The model tested in a manufacturing firm in Central Java by using an explanatory quantitative research design, this study attempts to test the relationship between the hypotheses built. By using the Amos 25 data analysis tool, 220 samples have been tested and analyzed using regression data analysis techniques as a statistical test. The results of this study provide an indication from a theoretical perspective that the hypothesis proposed in this study can be accepted significantly, it shows that the existence of various antecedents used by firm value described by each hypothesis is able to become a form of key factor for increasing firm value. This research has several limitations, among others, the various research variables used in this study have not been able to specifically, perhaps in the form of a derivation or in a concept that has more abstraction that is more critical to increase and value the firm. In addition, the sample used in this study is still too narrow because it only uses the manufacturing industry in the province of Central Java as a representation of the population of manufacturing companies used in this study. The oretically and managerially this research has been able to provide a form of evidence that new solutions can be used to increase the value of green concept-based companies and the sustainability of firm performance. can provide recommendations for business people both at managerial and owner levels to increase firm value based on the proposed path model, namely through green growth to sustainable corporate performance to firm value, green practice to green business to sustainable corporate performance, green practice to green business to firm value.